Moderating effect job satisfaction: Investigation transformational leadership on turnover intention - Didit Haryadi; Otosokhi Waruwu; Fariza Hashim (Institute of Accounting Research and Novation (IARN), 2026)
The identified gaps arose because previous research showed inconsistent results and rarely included job satisfaction as a moderator in the model of the influence of transformational leadership on turnover intentions. This study seeks to examine the influence of transformative leadership on employee turnover intentions, including variations in work satisfaction. This study employs quantitative methodologies pertinent to the objective of 103 employees at PT BFI Sector Tangerang Financing. The sample was meticulously gathered, comprising a total of 103 respondents. The data gathering was a questionnaire survey employing a point scale from 1 (strongly disagree) to 10 (strongly agree). The data analysis employed the SEM-PLS methodology, integrating external models, internal models, and bootstrap testing to validate three hypotheses. The results indicate that transformative leadership exerts a significant negative influence on turnover intention (b-0.353 sig 0.013). Moreover, job satisfaction exerts a substantial negative influence on turnover intention (b-0.341 sig 0.001). Moreover, work satisfaction serves as a moderated in the association between transformative leadership and turnover intention (b 0.369 sig 0.000). This study underscores the significance of management approaches that boost employee well-being and retention rates by improving leadership quality and fostering a supportive work environment. This research seeks to offer valuable insights for human resource management by integrating leadership components and work satisfaction to develop effective employee retention strategies. The moderating role of job satisfaction as a strengthening factor increases the influence of transformational leadership on turnover intentions, thus clarifying the mechanism of its influence in the organizational context.